Pengaruh Indikator Pertumbuhan Perusahaan, Kebijakan Hutang dan Kemampuan Menghasilkan Laba terhadap Kinerja Saham - Agus Afandi; Diantia Amendy; Dian Novianti (INOVASI, 2023)
The aim of this research is to examine the influence of company growth indicators, debt policy and profit-generating ability on stock performance in basic industrial and chemical sector companies listed on the Indonesia Stock Exchange (BEI) for the period 2017 - 2021. Company growth indicators are proxied by sales growth and growth. assets, debt policy is proxied by the debt to equity ratio (DER) and long term debt to equity ratio (LDER), the ability to generate profits is proxied by return on assets (ROA) and return on equity (ROE), stock performance is proxied by stock returns. The sample selection technique is purposive sampling method, research data is secondary data obtained from the Indonesia Capital Market Directory for the period 2017 - 2021. The data analysis method used is multiple regression analysis with the eviews 12.0 application tool. The research method stages consist of; descriptive statistics, panel data regression model selection, classical assumption testing, multiple regression analysis, hypothesis testing and conclusions. It is hoped that this research can contribute to writing scientific journals and be published in accredited scientific journals, Sinta. The results of the research show that the variables sales growth, asset growth, debt to equity ratio (DER), long-term debt to equity ratio (LDER) and return on equity (ROE) do not partially have a significant effect on stock returns, while the variable return on assets ( ROA) partially has a positive and significant effect on stock returns.